Ways of Structuring and Organizing an Archaeological Open-Air Museum - Clara Imeyer (EXARC Journal)
In February 2014 Clara Imeyer, student of International Tourism Management at the Hochschule Bremen, Germany, completed her Bachelor thesis with the title Ways of Structuring and Organizing an archaeological Open-Air Museum – Analysis of the Iron Age House (Eisenzeithaus Venne, Germany). This article is intended to provide an insight into her approach to this topic and present the most important results of her work.